PERBANDINGAN KOMPETENSI GURU PLH DALAM MEMBANGUN MODEL PEMBELAJARAN KREATIF DI SMP NEGERI AKREDITASI A DAN SMP NEGERI AKREDITASI B KOTA PADANG - Zelhendri Zen; Ahmad Johari Bin Sihes (Pedagogi: Jurnal Ilmu Pendidikan, 2016)
The purpose of this study is to analyze the comparison of teachers’ competence of Environmental Education Subject at State of SMP in Padang City to build and implement a creative learning model based on school accreditation status. Four indicators of creativity measured in the comparison of teachers’ competence to build and apply this creative learning model are 1.) measurement of teacher's competence comparison to build creative learning of fluency thinking element between SMPN with accreditation A and B, 2.) Measure teacher's competence to build creative learning of flexible thinking element between SMPN with accreditation A and B, 3.) Comparative measurement of teacher's competence to build creative learning of original thinking element between SMPN with accreditation A and B, and 4.) complementary measurement of teacher to build creative learning element of elaboration thinking between SMPN with accreditation A and B. Population in this Research are all teacher of Environmental Education Subject as much as 57 in SMPN A- accredited and 57 in SMPN B-accredited with a total of 114 teachers. The research instrument used questionnaires, interviews, observation and documentation. Data analysis was done by using descriptive statistics and inferential statistics consist of validity and reliability, normality, homogeneity and independent t-test. The result of the research shows that there is an increase of competence of environmental education subject teachers between SMPN A-accredited and B- accredited in building creative learning model 1) fluency thinking, 2) flexible thinking, 3) original thinking and 4) elaboration thinking) Teachers of SMPN with A- accredited is better competence to build creative learning model than Teachers of SMPN with B- accredited in Padang city. This is due to the differences in the number of training, the difference in the facilities and learning infrastructure, the difference of the students input when the selection comes in